The state of play for contact training and coaching in women's rugby - Stodter, A.; Dane, K. (European Journal of Sport Science, 2024)
This article aims to review and comment upon the current "state of play" for research around contact and tackle training in women's rugby, covering tackle injury risk, match contact demands, players' experiences of contact coaching and contact skill preparation. In women's rugby, the tackle is the most common match technical-physical contest, accounting for around two-thirds of all injuries and carrying the greatest injury burden. Players' experience and technical abilities are key determinants of tackle safety and performance. Despite this, there is limited research available that connects insight into women's rugby contact demands with the how and why of effective tackle and contact training and coaching in context. This review suggests that adapting and adopting progressive tackle skill training frameworks and gender-responsive coaching practices can aid tackle skill learning in women's rugby. Creative transdisciplinary research and more effective translation and implementation activities that take place within the vibrant and growing context of women's rugby can enhance science and safety whilst working as a medium for social change.